The Social Construction on Financial Reporting of Small and Medium Scaled Production House - Safiera F. Azzahra; Falikhatun (Fakultas Ekonomi dan Bisnis, Universitas Udayana bekerjasama dengan Ikatan Sarjana Ekonomi Cabang Bali, 2024)
This study investigates the role of financial reporting in small and mediumsized film production houses, focusing on its economic significance and the social construction surrounding its practices. Utilizing a constructivist approach with grounded theory methodology, the research comprises indepth interviews, observations, and documentation, further analyzed through triangulation. The findings reveal that these production houses view financial reporting as essential for business sustainability, with stakeholder theory explaining the need for both financial and non-financial information to meet internal and external requirements. Specifically, financial reports typically include simple income statements, cash flows, and balance sheets with tangible assets and trade payables, alongside nonfinancial data. These results offer a foundation for further studies and insights for financial reporting regulations within the film industry. However, the research scope is limited to specific regional practices and a narrow observational timeframe.